Maximal isometric handgrip strength and endurance differences between elite and non-elite young judo athletes - Bonitch-Gongora, J. G.; Almeida, F.; Feriche, B.; Padial, P.; Bonitch-Dominguez, J. G. (Archives of Budo, 2013)
Judo is a combat sport in which the maintenance of handgrip strength is essential because the judokas repeat this action continuously during the struggle for grip. While descriptions of maximal isometric handgrip strength in judokas are relatively common, few data exist concerning the ability to resist successive isometric contractions in the hands and its relation to performance. The aim of this study was the differences and similarities between elite and non-elite young judokas in terms of maximal isometric handgrip strength and their endurance to this strength. Material and Methods: Seventy-three adolescents participants from three national (elite) and one regional team (non-elite) were tested. The maximal isometric handgrip strength was recorded during a maximum test of 6 s with an electronic Digimax dynamometer. The endurance to the isometric handgrip strength was measured by a test consisting of 8 contractions of 10 s each alternating with 10 s of passive rest, and was also recorded with the same machine. Results: The endurance test decreases the relative and mean isometric handgrip strength of male and female judokas (p=0.01), irrespective of their competitive level. However, male and female elite judokas developed higher levels of relative isometric handgrip strength in the maximum test and during all contractions of the endurance test than non-elite judokas (p=0.01 for both sexes). In all cases, the non-elite group took longer to reach the maximal isometric handgrip strength (p=0.05). Conclusions: Maximal isometric handgrip strength and the endurance to this strength were able to distinguish between elite and non-elite young judokas. Coaches should include conditioning programs for both maximal isometric handgrip strength and the ability to resist successive isometric contractions to maximize performance.